Pemanfaatan Aplikasi Mitigasi Bencana Berbasis Android dalam Pembelajaran IPS - Slamet Slamet; Suwarno Suwarno (Proceedings Series on Social Sciences & Humanities, 2022)
Geological location of Indonesia is at the confluence of active plates and 2 active mountain lines and is in a tropical climate, so most of Indonesia is prone to natural disasters. There are various kinds of natural disasters in Indonesia so that Indonesia is known as a Natural Disaster Laboratory. The Indonesian people, especially the young generation of the nation's heirs, really need to get disaster mitigation education as an effort to create a disaster-resilient generation. Disaster mitigation education for millennial generation students must be adjusted, according to Ki Hajar Dewantara's message "educate children in a way that is in accordance with the demands of nature and the times". 21st century learning is marked by advances in information technology for critical, creative, collaborative and communication thinking. Literature study to examine the development of information technology media about android-based disaster mitigation applications available with the aim that students have awareness of their own existence and are able to interact with their immediate environment, able to analyze the relationship between regional geographical conditions and their relation to disaster mitigation.